Interactions of the aryl hydrocarbon receptor with inflammatory mediators: beyond CYP1A regulation - Vondrácek, Jan; Umannová, Lenka; Machala, Miroslav (Current drug metabolism, 2011)
The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor, which plays a major role in toxic effects of environmental pollutants. It is a pivotal regulator of several xenobiotic-metabolizing enzymes (XMEs), and is now considered to play an important role also in control of cell cycle, apoptosis and cell differentiation. The accumulating evidence suggests that there exists a multiple crosstalk between AhR activation and the signaling pathways activated by inflammatory mediators, such as nuclear factor-κB, a pleiotropic transcription factor controlling the immune/inflammatory responses. In this review, we summarize the current knowledge about the interactions of AhR with inflammatory mediators leading to deregulation of the AhR-dependent XMEs, as well as the evidence pointing to the role of AhR in modulation of inflammatory signals. These include altered expression of proinflammatory cytokines, such as tumor necrosis factor-alpha or interleukin-6, and deregulation of expression/activity of principle enzymes producing inflammatory mediators, such as cyclooxygenase-2. Recent studies also indicate that various classes of AhR ligands may differentially modulate AhR-dependent toxic responses and inflammation, which opens an interesting opportunity for a targeted synthesis of AhR ligands with anti-inflammatory properties. Although the role of activated AhR in the regulation of inflammation is still far from being completely understood, the close interactions between AhR and inflammatory signaling evidently can play a significant role in immune dysfunctions, metabolism of xenobiotics or carcinogenesis. The current review will focus mostly on the interaction of AhR and inflammation relative to mechanisms associated with the pathology of carcinogenesis.
Keywords: receptory aromatických uhlovodíků; Inflammation; xenobiotika; mediátory zánětu; Gene Expression Regulation, Enzymologic; signální transdukce; Signal Transduction; zánět; Animals; lidé; aromatické hydroxylasy; Humans; Xenobiotics; regulace genové exprese enzymů; Aryl Hydrocarbon Hydroxylases; zvířata; Inflammation Mediators; antiflogistika; Anti-Inflammatory Agents; Receptors, Aryl Hydrocarbon